The Amhara of Ethiopia: Embracing and Using Imposed Identity to Resist Injustice - Melaku, Tadesse (Genealogy (Basel), 2024)
Ethnic identities often solidify in response to perceived or actual injustices endured by groups. Historically, Amharic-speaking people in Ethiopia have resisted ethnic identification, aligning instead with broader Ethiopian nationalism. However, the rise of extreme ethnonationalist forces in the country has subjected the group to negative narratives, violence, and marginalisation, associating them with past state domination. In response, the Amhara have increasingly embraced ethnic identity as a form of self-defence. This study employs thematic analysis to explore the experiences of the Amhara people and the subsequent emergence of their collective identity, including the rise of resistance movements. Despite this new alignment, Amhara elites and activists paradoxically maintain a strong commitment to Ethiopian unity, reflecting a complex duality in their socio-political stance. This balancing act illustrates their struggle to survive while remaining loyal to national unity. The article argues that sustained violence and marginalisation have catalysed the rise of Amhara group consciousness, transforming Ethiopia’s political landscape. This study offers broader insights into how group mentality can emerge as a response to systematic and sustained injustice and the implications this has for redefining power politics in Ethiopia and beyond, providing insights for policymaking and future research.